Estetika Pertunjukan Gender Wayang secara Virtual - Ni Putu Hartini; Ni Made Haryati (Universitas Hamzanwadi, 2023)
Gender Wayang is an old Balinese gamelan that uses a 5-tone selendro barrel. Gender Wayang in its presentation in this pandemic era has a new model so that it becomes an attraction to be discussed. Due to the Covid-19 pandemic outbreak, the change in Gender Wayang performances which are generally held in person has been changed to a virtual performance. This study aims to find out the aesthetic elements in the virtual Gender Wayang performance and the meaning contained in the virtual Gender Wayang performance. This virtual performance was carried out in an effort to treat the longing of art lovers, especially the Gender Wayang gamelan. Gamelan Gender Wayang is one of the primadonnas among the community, especially children, teenagers both from elementary school, junior high school, high school and college. The research method used is a qualitative method with data collection techniques through participant observation and interview methods. The result obtained is the aesthetics and meaning contained in the virtual Gender Wayang performance. With the virtual Gender Wayang performance, it can be used as a forum in presenting artworks in fighting the Covid-19 pandemic that we are facing together.